The spirit with no anus and the pots that fart: ceramics of life and death in Northwest Amazonia - Stephen Hugh-Jones (Journal de la Société des Américanistes)
This paper takes as its starting point the story of a spirit with no anus whose inability to fart leads to his death and transformation into clay. In particular, it examines the relationship between pottery trumpets associated with this spirit (played in exchange ceremonies) and bark Jurupary trumpets and suggests that the two instruments stand in a relationship of “flesh” and “bone”. Uncovering this parallelism provides an opportunity to revisit noise, putrefaction, and beer in Northwest Amazonian mortuary rituals, where other types of pottery trumpets are used in conjunction with Jurupary trumpets. The paper concludes with a brief discussion of the relevance of these mythical and ritual materials to Amazonian archaeology and the interpretation of anthropomorphic burial urns.